(untitled) - Houpis, Constantine H. (New York, 1985)
This book intergrates control theory with computer implementation. The root-locus method is utilized as the major control sysem design technique throughout the text. It also emphasizes the use of a computer-aided design package to accomplish much of the design work for sampled-data control systems. Also, it stresses the impact of small samling times upon the design calculations and digital controller accuracy.
Keywords: Digital control systems,Hệ thống điều khiển số